2018
DOI: 10.1002/mbo3.636
|View full text |Cite
|
Sign up to set email alerts
|

Cheating, facilitation and cooperation regulate the effectiveness of phage‐encoded exotoxins as antipredator molecules

Abstract: Temperate phage encoded Shiga toxin (Stx) kills the bacterivorous predator, Tetrahymena thermophila , providing Stx + Escherichia coli with a survival advantage over Stx − cells. Although bacterial death accompanies Stx release, since bacteria grow clonally the fitness benefits of predator killing accrue to the kin of the sacrificed organism, meaning Stx‐mediated protist killing is a form of self‐destructive cooperation. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
(88 reference statements)
0
8
0
1
Order By: Relevance
“…In the human colon, Stxs may be released by EHEC in free form through phage-induced bacterial cell lysis by decaying bacteria, since no specific secretion system has been identified so far for the active release of Stxs [ 140 , 221 , 257 ]. Noteworthy, liberated Stx phages can infect not only E. coli but also other types of bacteria, such as Citrobacter freundii or Enterobacter cloacae , and may “abuse” susceptible bacteria in the population as surrogates to multiply toxin and phage production [ 376 , 377 , 378 , 379 ]. Thus, Stx-encoding bacteriophages have to be considered extremely mobile genetic elements that play a pivotal role in the (1) expression of Stx, (2) horizontal gene transfer, and more generally (3) genome diversification acting as “genomes in motion”, thereby strengthening the severity of STEC infections as prophesized by the Karch research consortium in 2004 [ 380 ].…”
Section: Ehec-caused Diseases and Damage Of Human Target Cellsmentioning
confidence: 99%
“…In the human colon, Stxs may be released by EHEC in free form through phage-induced bacterial cell lysis by decaying bacteria, since no specific secretion system has been identified so far for the active release of Stxs [ 140 , 221 , 257 ]. Noteworthy, liberated Stx phages can infect not only E. coli but also other types of bacteria, such as Citrobacter freundii or Enterobacter cloacae , and may “abuse” susceptible bacteria in the population as surrogates to multiply toxin and phage production [ 376 , 377 , 378 , 379 ]. Thus, Stx-encoding bacteriophages have to be considered extremely mobile genetic elements that play a pivotal role in the (1) expression of Stx, (2) horizontal gene transfer, and more generally (3) genome diversification acting as “genomes in motion”, thereby strengthening the severity of STEC infections as prophesized by the Karch research consortium in 2004 [ 380 ].…”
Section: Ehec-caused Diseases and Damage Of Human Target Cellsmentioning
confidence: 99%
“…Because its production requires a lytic bacteriophage, Shiga toxin presents a kind of double-edged sword for cooperating bacterial populations. Shiga toxin is produced during lytic replication, and release of the toxin is accompanied by the death of the producer and simultaneous release of infectious Stx virions (56). A meta-analysis of the Stx literature revealed that under more natural conditions (i.e., not conditions such as high concentrations of mitomycin C), Stx prophage induction occurred in approximately 1% of the bacterial population (57).…”
Section: Bacteriophages Bacteria and Toxic Altruismmentioning
confidence: 99%
“…If Stx enters the lytic cycle, cheaters are converted into Shiga toxin producers and are subsequently lysed and removed from the population. Alternatively, if cheaters are lysogenized by Stx, Shiga toxin genes are preserved in the bacterial population, contributing to the maintenance of this cooperative behavior (56).…”
Section: Bacteriophages Bacteria and Toxic Altruismmentioning
confidence: 99%
“…Besides group B colicins, a number of other substances, including DNA and host-directed toxins are known to be released by temperate phage-mediated lysis ( 35 , 50 52 ). On the one hand, the lytic/lysogenic phage system mediates lysis; on the other hand, the phenotype (colicin, Shiga toxin, DNA release) confers fitness benefits to the surviving population.…”
Section: Discussionmentioning
confidence: 99%